2021
DOI: 10.1016/j.asmr.2021.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Resection on Posterior Talofibular Ligament Integrity for Posterior Ankle Impingement Syndrome: A Cadaveric Study

Abstract: The purpose of this study was to evaluate the attachment areas of the posterior talofibular ligament (PTFL) on the posterolateral tubercle of the talus and the remaining PTFL attachment areas after consequential bony excision. Methods: Thirty fresh cadaveric ankles were dissected to study the proximal and distal attachment of the PTFL and separated the PTFL into anterior and posterior bundles. The description of the PTFL footprint and the anatomic landmarks from the surrounding structures were analyzed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Third, it was difficult to distinguish retrospectively between a fractured posterior talar process and an os trigonum. The research of Inchai et al 20 showed that the posterior bundle of the posterior talofibular ligament (PTFL) is the main bundle on the talar footprint area. To maintain the majority of the attachment of the PTFL, resection of the posterolateral process could be performed to the bottom of the flexor hallucis longus (FHL) tendon groove.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it was difficult to distinguish retrospectively between a fractured posterior talar process and an os trigonum. The research of Inchai et al 20 showed that the posterior bundle of the posterior talofibular ligament (PTFL) is the main bundle on the talar footprint area. To maintain the majority of the attachment of the PTFL, resection of the posterolateral process could be performed to the bottom of the flexor hallucis longus (FHL) tendon groove.…”
Section: Discussionmentioning
confidence: 99%